2018
DOI: 10.1016/j.appet.2017.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of access determines influence of junk food diet on cue sensitivity and palatability

Abstract: These data demonstrate that the pattern of junk food exposure differentially alters the hedonic impact of palatable foods and susceptibility to the motivating influence of cues in the environment to promote food-seeking actions when sated, which may be consequential for understanding overeating and obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 133 publications
(148 reference statements)
0
7
0
Order By: Relevance
“…Cue-invigorating food-seeking may be considered adaptive, but the maladaptive eating in the absence of hunger forms the basis for the FA hypothesis. It has been shown that limited or intermittent access to highly palatable foods increase cue-reactivity to these foods, which has implications for the consequences of extreme dieting behavior in humans ( 85 ).…”
Section: Food “Reward” and Accumbens Dopaminementioning
confidence: 99%
“…Cue-invigorating food-seeking may be considered adaptive, but the maladaptive eating in the absence of hunger forms the basis for the FA hypothesis. It has been shown that limited or intermittent access to highly palatable foods increase cue-reactivity to these foods, which has implications for the consequences of extreme dieting behavior in humans ( 85 ).…”
Section: Food “Reward” and Accumbens Dopaminementioning
confidence: 99%
“…In a related study, we found that rats given intermittent junk-food access were also impaired in a distinct, nonspecific version of the Pavlovian-to-instrumental transfer task ( 8 ). In that study, rats that had been given intermittent access to a junk-food diet showed indiscriminant instrumental food-seeking behavior in response to both food-paired and unpaired cues, unlike chow-fed rats, which showed a selective increase in responding during trials with the food-paired cue.…”
Section: Discussionmentioning
confidence: 93%
“…Overeating and obesity seem to represent a failure of the multifaceted homeostatic processes that regulate energy balance and nutritional diversity ( 4 ), and there is growing evidence that repeated exposure to a junk-food diet can exacerbate the situation by further dysregulating feeding and food seeking. Specifically, animal studies have shown that poor diets (e.g., refined, high-fat, or high-sugar diets) can cause persistent aberrations in behavioral control and cognition, resulting in impulsive decision making ( 5 , 6 ), motivational impairments ( 7 ), and altered food reward liking and craving ( 8 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…The number of bursts reflects the incentive motivation triggered by cues because it indicates the activation of responses (Johnson, Sherwood, Smith, Gallagher, & Holland, ; Johnson et al., ; Smith, ). The size of the bursts reflects the hedonic impact of reward (Dwyer, ; Kosheleff et al., ; Mendez, Ostlund, Maidment, & Murphy, ; Ostlund, Kosheleff, Maidment, & Murphy, ), whereas the intraburst lick speed is an indicator of licking‐associated motor control (Gramling & Fowler, ; Gramling, Fowler, & Collins, ).…”
Section: Discussionmentioning
confidence: 99%